2019
DOI: 10.1111/tmi.13206
|View full text |Cite
|
Sign up to set email alerts
|

Co‐infections with Plasmodium, Ascaris and Giardia among Rwandan schoolchildren

Abstract: ObjectivesCo‐infections with Plasmodium, Ascaris and Giardia are common in sub‐Saharan Africa but epidemiological and clinical data are rare. We examined factors associated with co‐infections and their clinical manifestation among Rwandan schoolchildren.MethodsSchoolchildren aged 6–10 years attending 12 schools in Huye district, Rwanda, were recruited preceding routine deworming. Data on socioeconomic status (SES) and children′s histories were obtained, and children were clinically and anthropometrically exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…( 2020 ) in Kenya (46.5; 13.0%), Geus et al . ( 2019 ) in Rwanda (36.0; 7.1%) and El Fatni et al . ( 2014 ) in Morocco (12.5; 3.0%) reported that microscopy detected more Giardia spp.-positive infections as compared to molecular methods.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…( 2020 ) in Kenya (46.5; 13.0%), Geus et al . ( 2019 ) in Rwanda (36.0; 7.1%) and El Fatni et al . ( 2014 ) in Morocco (12.5; 3.0%) reported that microscopy detected more Giardia spp.-positive infections as compared to molecular methods.…”
Section: Discussionmentioning
confidence: 86%
“…Whereas in Gambia,Goudal et al (2019) andSullivan et al (1991) reported that microscopy (20.1 and 48.6%) detected more Giardia spp.-positive infections as compared to serological tests (18.5 and 30.6%) in that order respectively. Furthermore,Emisiko et al (2020) in Kenya (46.5; 13.0%),Geus et al (2019) in Rwanda (36.0; 7.1%) and El Fatni et al (2014) in Morocco (12.5; 3.0%) reported that microscopy detected more Giardia spp.-positive infections as compared to molecular methods. Remarkably, Becker et al (2015) reported similar detection prevalence (28.7%) by microscopy, copro-antigen and molecular methods in Côte d'Ivoire.…”
mentioning
confidence: 98%
“…A survey of Plasmodium, Ascaris and Giardia infection in Rwandan schoolchildren showed that parasitic coinfections were common, but the clinical picture was mostly associated with Plasmodium infection and not modified by Ascaris or Giardia coinfection. However, malnutrition was more pronounced in children coinfected with Ascaris and Giardia compared to individuals with single infections (Geus et al, 2019). Similarly, a study in subtropical Argentina observed an association between stunting in older children and the presence of enteric parasites, multi-parasitism and giardiasis (Rivero et al, 2018).…”
Section: Sth and Giardia Infectionmentioning
confidence: 94%
“…Despite the fact that Giardia shares the small intestinal habitat with Ascaris, hookworms and threadworms, relatively few studies tested for potential interactions between enteric nematode and Giardia infections. Furthermore, although the prevalence of Giardia infection is often high in areas where STH and/or schistosome infections are highly endemic (Fofana et al, 2019;Geus et al, 2019;Archer et al, 2020), data on potential interference of immune responses directed against the two types of parasites are largely lacking.…”
Section: Sth and Giardia Infectionmentioning
confidence: 99%
“…Malaria is caused by the mosquito-borne eukaryotic protozoan parasites of the genus Plasmodium (Plasmodium falciparum, Plasmodium vivax, Plasmodium malariae, and Plasmodium ovale). In many parts of the world malaria, helminths and Giardia are endemic in the same areas and are often co-morbid (Geus et al, 2019). Malaria and helminth/Giardia parasite syndemics today have been linked to climatic shifts, living conditions, subsistence strategies, and low socioeconomic status.…”
Section: The Malaria and Gastrointestinal Parasite Syndemic In Early ...mentioning
confidence: 99%